Development of ultra low field magnetic resonance imaging for diagnosis of hydrophalus in developing countries - Obungoloch, Johnes (The Pennsylvania State University, 2017)
Access to Medical imaging technologies and services still remain a challenge in low and middle income countries (LMICs). The most common imaging modalities available are X-ray technologies and ultrasound, none of which is appropriate for imaging the brain. Diagnosis and monitoring of mental and brain illnesses such as epilepsy, hydrocephalus, and trauma rely mainly on computed tomography (CT) even though they are known to have adverse e ects [1] especially with repeated exposures as is required in neuro-surgical interventions. Conventional magnetic resonance imaging (MRI), a relatively safer technology than CT is very expensive for LMICs to a ord. The capital costs of installing a 3 T MRI system can be as high as $3 million [2]. On top of the high procurement and installation costs, other requirements such as cryogens and technical expertise have prevented the proliferation of MRI in developing countries. Premised on this background, this thesis explains the development of an ultra-low eld MRI suitable for the diagnosis of hydrocephalus in the developing world. Parameters considered for the suitability of this MRI include low cost, low power and technical requirements, portability and exibility in siting. To meet the aims of this project, an ultra-low eld MRI system capable of admitting an adult head was constructed at a cost of $30,000. This MRI system requires no cryogens, has maximum power requirement of 1.5 kW, weighs 125 kg and can operate in an un-shielded room. Images of vegetables were acquired with the system operated at 113 kHz.
Keywords: Medical imaging technologies; X-ray technologies; Ultrasound; Magnetic resonance imaging (MRI); low and middle income countries (LMICs)